The chronicle of Ibn al-Athir for the crusading period from al-Kamil fi’l-ta’rikh, part 1 : the years 491-541/1097-1146 the coming of the Franks and muslim response - Ibn al-Athir, Izz al-Din, 1160-1233 (Aldershot)
viii, 401 s.